Efficiency of the novel TP/LLDPE nanocomposite in killing multi-drug resistant pathogens. (11th November 2021) - Mohamad Faudzi, Ku Nur Izzati Ku; Sreekantan, Srimala; Mydin, Rabiatul Basria S M N; Basiron, Norfatehah; Hassan, Mohd; Nabi, Arshid
Abstract: A series of linear low-density polyethylene (LLDPE) polymer nanocomposites with g-C3 N4 -ZnO/TiO2 ternary photocatalyst (TP) at 1 wt%, 5 wt%, 7 wt%, and 10 wt% was synthesised by melt blending method. The structural properties, chemical properties, photocatalytic and antibacterial activities were evaluated in this study. The addition of TP reduces the degree of crystallisation of the LLDPE nanocomposite. The OH functional group on TP increases the polarity, thus improving the LB broth's wettability for bacterial adhesion, which enhances the inactivation effect. A minimum of 0.3 mg l −1 of Zn 2+ together with · OH and · O 2 − are required to inactivate the MDR pathogens. More than 99% inactivation in 6 h can be achieved against MDR pathogens for 5 wt% TP loading while 12 h for 1 wt% TP loading in LLDPE nanocomposites. The photocatalytic performance of the zinc oxide and titanium oxide for the degradation of methylene blue has exhibited good photocatalytic properties. The obtained results have confirmed the photocatalytic activity for the bactericidal effect of TP/LLDPE composites was dominant by · OH and · O 2 − while slightly by holes. The purpose of this work is to obtain the optimum amount of ternary photocatalyst incorporated with LLDPE and incubation time required to kill a broad spectrum of multidrug-resistant (MDR) pathogens like E. coli, S. aureus, B. subtilis, S. flexneri, B. cereus, and K. pneumoniae . The LLDPE nanocomposite with 1 wt% showed >99% inactivation against the MDR pathogens within 12 h while with 5 wt%, it takes 6 h. The synergic action of structural properties such as crystallinity, wettability, chemical structure on the reactive oxygen species (ROS), and Zn ion release for inactivation against the MDR pathogens is deliberated.